PEDAGOGY OF COMPETENCIES AND TEACHING WORK: TENSIONS BETWEEN INSTRUMENTAL TRAINING AND THE EMANCIPATORY PERSPECTIVE - Betiate, Francieli Aparecida; Derisso, José Luis (Seven Editora, 2025)
This article analyzes the influence of the Pedagogy of Competencies on the reconfiguration of teaching work and contemporary conceptions of human development, highlighting how educational policies, marked by administrative logic and adaptation to market demands, subordinate pedagogical practices to a productivist bias. The article discusses the impact of this model on the intensification of teachers’ tasks, the precariousness of their autonomy, and the dissemination of pragmatic perspectives that promote individual blame for academic failure. It also highlights the tension between technical training and critical development, clarifying that the pursuit of immediate results neglects structural conditions and impedes the consolidation of an emancipatory perspective. To this end, an analysis is conducted, based on a literature review, which allows us to understand the effects of the Pedagogy of Competencies on pedagogical practices and teacher development. Finally, the importance of objective working conditions is highlighted, linked to the valorization of a critical pedagogy that supports a democratic and humanizing educational project. DOI: https://doi.org/10.56238/sevened2025.038-009